Cookies & Chill / Muhammad Izzat Rosnan - Rosnan, Muhammad Izzat (2019)
Cookies & Chill is a sole proprietorship business who started the business on 26thSeptember 2019. Since then, Cookies & Chill got many orders from customers who bought this product because of the luxurious tastes that comes with an affordable price. Cookies &Chill use social media as a medium to introduce, promote and sell the product. Currently, the business use Facebook as a main medium to promote and sell chocolate chip cookies.